The Effect of Trauma Care on the Temporal Distribution of Homicide Mortality in Jefferson County, Alabama. Issue 3 (March 2014) - Griffin, Russell L.; Davis, Gregory G.; Levitan, Emily B.; Maclennan, Paul A.; Redden, David T.; Mcgwin, Gerald
The distribution of time from acute traumatic injury to death has three peaks: immediate (less than or equal to one hour), early (6 to 24 hours), and late (days to weeks). It has been suggested that coordinated trauma care dampens the late peak; however, this research may be more reflective of unintentional than intentional deaths. This study examines whether a coordinated trauma system (TS) alters the temporal distribution for assault-related deaths. Data were obtained from homicides examined by the Jefferson County Coroner's/Medical Examiner's Office from 1987 to 2008. Homicides were categorized—based on year of death—as occurring in the presence of no TS, during TS implementation, in the early years of the TS, or in a mature TS. The temporal distribution of homicide mortality was compared among TS categories using a χ 2 test. A Cox Markov multistate model was used to estimate proportional changes in the temporal distribution of death adjusted for assault mechanism. With a TS, after adjusting for assault mechanism, a lower proportion of homicide victims survived through the first hour (hazard ratio [HR], 0.75; 95% confidence interval [CI], 0.54 to 1.03) and from one to six hours (HR, 0.68; 95% CI, 0.49 to 0.96). Additionally, the presence of a TS was associated with a proportional decrease in deaths after 24 hours ( P = 0.0005). These results suggest that a trauma system is effective in preventing late homicide deaths; however, other means of preventing death (such as violence prevention programs) are needed to decrease the burden of immediate homicide-related deaths.